2013
DOI: 10.1155/2013/351062
|View full text |Cite
|
Sign up to set email alerts
|

Does Propolis Help to Maintain Oral Health?

Abstract: Propolis, known also as bee glue, is a wax-cum-resin substance which is created out of a mix of buds from some trees with the substance secreted from bee's glands. Its diverse chemical content is responsible for its many precious salubrious properties. It was used in medicine already in ancient Egypt. Its multiple applications during the centuries have been studied and described in details. The purpose of this study is to present the possible use of propolis in treatment of various diseases of oral cavity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 79 publications
0
65
0
6
Order By: Relevance
“…Greater scientific knowledge of the chemical composition of various types of propolis has helped envision their potential use and application in dental practice. 8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionmentioning
confidence: 99%
“…Greater scientific knowledge of the chemical composition of various types of propolis has helped envision their potential use and application in dental practice. 8,9,26,27 Previous studies have reported the strong antimicrobial activity of propolis against several bacteria of the oral m icrobiome, i ncludi ng S. mutans. 1,2,28,29,30,31 As confirmed in our study, propolis and some of its isolated compounds, such as apigenin and tt-farnesol, 11 have been found to display a major effect on microbial virulence (e.g., polysaccharide production and acid tolerance), rather than affecting unspecific or specific microbiome viability, considered a highly desirable quality.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds are produced by bees from bee secretions, beeswax, plant exudates, and other plant parts collected from the surrounding flora (Bankova, 2005;Scazzocchio et al, 2006;Wiȩckiewicz et al, 2013). Propolis contains a variety of compounds, some of which are terpenes, flavonoids and other phenolics (Marcucci, 1995;Bankova et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Literature indicates that propolis is associated with a number of important biological activities including antimicrobial, antioxidant, anticancer, hepatoprotective, anti-inflammatory, immunostimulant, anticariogenic, antiprotozoan, allergenic, antibrowning, antidiabetic and antitumour activities (Ophori et al, 2010;Siripatrawan et al, 2013;Wagh, 2013;Wiȩckiewicz et al, 2013;Wojtyczka et al, 2013a, b;Omar et al, 2016). Furthermore propolis has been reported to exhibit synergism with a number of antibiotics against various bacteria species (Stepanović et al, 2003;Fernandes Júnior et al, 2005;Scazzocchio et al, 2006) and to be active against methicillin resistant Staphylococcus aureus [MRSA] (Darwish et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies with propolis prove its antimicrobial, antioxidant, anti-inflammatory, immunomodulatory, hypotensive, healing, anesthetic, anticancer, anti-HIV and anticariogenic properties [13, 15, 21], allowing another way to use it in Dentistry, as in restorative dentistry, propolis can be used to decrease permeability of the dentin and to direct pulp capping in order to create restorative dentin [22]. …”
Section: Discussionmentioning
confidence: 99%